Phylogenetic analyses of distantly related clades of bent-toed geckos (genus Cyrtodactylus) reveal an unprecedented amount of cryptic diversity in northern and western Thailand - Chomdej, Siriwadee (Sci Rep, 2021)
Cyrtodactylus species are the most diverse of the geckos and are widely distributed in Southeast Asia, including Thailand. However, their patterns of distribution, especially in northern and western parts of Thailand, remain unknown because few Cyrtodactylus species in these regions have been described. Thus, a data set of mitochondrial NADH dehydrogenase 2 (ND2) gene and flanking tRNAs from Cyrtodactylus found in northern and western Thailand, including contiguous areas, was assembled to elucidate phylogenetic relationships and identify the distribution patterns of these geckos. The results showed four well-supported clades, a northwestern clade (A), a northern clade (B), a western clade (C), and a special clade characterized by specific morphological features (D). Clades A–C were grouped with strong support by the geography of their localities from northern Thailand (Mae Hong Son and Chiang Mai Provinces) along the Tenasserim mountain ranges to Phang-Nga Province, Thailand. Clade D is a distinct clade of Cyrtodactylus species characterized by a tuberculate and prehensile tail and distributed widely in mainland Southeast Asia. Overall, the results suggest a pattern of geographic separation and distribution of Cyrtodactylus in northern and western Thailand. Additionally, this study provides evidence of a hidden biodiversity of Cyrtodactylus in these regions.